ENVIRONMENTAL-BALANCED SCORECARD DAN ETIKA BISNIS ISLÂM (Suatu Sintesis Manajemen Strategi dalam Persaingan Global) - Rudy Haryanto Rudy Haryanto (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2011)
Abstract: Business activity is an integral part of economic discourse. Islamic economy system starts from ethical awareness. For its viability, a company runs an old fashioned-management, it is a material-prosperity attainmnet oriented. However, it results a social contradiction. In Islamic ethic, a business must combine material and moral indicators emphesizing profit and expediency harmonies. Islamic business must be on the basis of natural and human resources that is moved by a motivation of dynamic devotion. Thus, it is  significant to have a management strategy that are religious, morality, and humanity oriented. Furthermore, the paradigm change that company goal maintaining the financial aspect change into social and environmental aspects is certain.   Key Words: Manajemen srategis, etika, perusahaan, lingkungan, dan Balanced Scorecard